Characteristics vs. requirements on a preindustrial neighbourhood: notes about the Trinas Neighbourhood - Mourão, Joana Fazenda Mendes (2019)
After more than 250 years the urbanization of the Trinas do Mocambo Convent land can still be seen as a successful urban development operation, showing adaptability over time, due to the high durability of the buildings that make up the “Trinas Neighbourhood”. These eighteenth-century buildings, which could fit into the landscape of current housing architecture in Lisbon at the time, have a set of features that have remained over time. This article seeks to identify some features and values of this neighbourhood that justify its integrity and efficiency. It also describes some recent transformations, identifying drivers and highlighting impacts to which this heritage is submitted, while analysing how certain technical and social requirements may influence the rehabilitation of this pre-industrial historical, architectural and urban heritage.